Advanced groundwater potential and contamination vulnerability assessment using integrated GIS-based AHP techniques: A case study from the Bizerte watershed, Tunisia - Cyrine Belhadj; Rihab Riahi; Abdelaziz Sebei; Sinda Sifi; Noamen Rebai (Environmental and Sustainability Indicators)
Sustainable management and monitoring of groundwater resources are critical for ensuring their availability for drinking, agriculture, and industry worldwide. In Bizerte, Tunisia (Southwest Mediterranean region), this need is particularly urgent due to rising demand and contamination risks, aligning with Sustainable Development Goal 6 (SDG 6), which seeks to ensure the availability and sustainable management of water and sanitation for all. This research aims to enhance groundwater management and assess contamination risks in Bizerte using the Analytic Hierarchy Process (AHP). A multidisciplinary approach was adopted, integrating multi-criteria analysis and a spatially referenced hydrogeological information system. Eight thematic layers, geomorphology (0.15), slope (0.10), lineament density (0.12), drainage density (0.10), land use/land cover (0.08), precipitation (0.20), lithology (0.15), and soil (0.10) were analyzed for their impact on groundwater availability. Weights were assigned via an AHP-based pairwise comparison matrix and integrated using Geographic Information System (GIS) technology to generate a groundwater potential map. The analysis revealed that approximately 60% of the area has significant groundwater potential, with 30% classified as high potential zones and 30% as moderate potential zones. Vulnerability to contamination was assessed, showing that 20% of the area is at risk, primarily due to agricultural activities, industrial discharges, and inadequate waste management. The results highlighted the need for continuous monitoring and effective management strategies, underscoring the importance of a holistic approach in groundwater management to provide a robust decision-making framework.